Potency of Purple Yam (Dioscorea alata L) as an Immunomodulatory Agent - Makiyah, Sri Nabawiyati Nurul; Djati, Muhammad Sasmito (Berkala Kedokteran, 2018)
Abstract: Purple yam tuber (Dioscorea alata L.) is one of tubers that has not been used optimally. One of the nutrients contained in Dioscorea species is Saponin Steroid. This paper aims to examine the potential of Steroid Saponin in purple yam tuber (Dioscorea alata L.) as an immunomodulatory agent. The method is by reviewing from various literatures. This article found that Steroid Saponin in purple yam tuber (Dioscorea alata L.) had a potency as an immunomodulatory agent.Â Keywords: Purple yam tuber (Dioscorea alata L), Steroid Saponin, Immunomodulatory